Perbandingan Kecepatan Lari 50 Meter pada Peserta Didik Umur 9 Tahun Antara Laki Laki dan Perempuan Madrasah Ibtidiayah An Nur Tondano - Isti Dikari; Agustinus R. J. Sengkey; Djony. A. Sunkudon (STIKES Columbia Asia Medan, 2025)
This study aims to examine the differences in 50-meter running speed between 9-year-old students, specifically between boys and girls at Madrasah Ibtidiayah An Nur Tondano. The research employs an ex post facto design with a sample of 30 students selected through simple random sampling, comprising 15 boys and 15 girls. Data were collected through a 50-meter sprint test, with time measured using a stopwatch accurate to one-tenth of a second. The research hypothesis posits that there is a significant difference in running speed between the two groups, with the expectation that boys will demonstrate superior performance compared to girls. Data analysis was conducted using an independent-samples t-test at a significance level of α = 0.05. The results revealed that the average running time for boys was lower than that for girls, indicating that boys have significantly higher running speeds. These findings provide important insights into the differences in motor abilities between boys and girls at this age and can serve as a basis for developing more adaptive physical education strategies and differentiated training programs tailored to the characteristics of each group.